Pengaruh Kompetensi Profesional Guru PAK Terhadap Minat Belajar Siswa Kelas IX SMP Negeri 2 Nainggolan Tahun Ajaran 2023/2024 - Maria Sinaga (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this study is to determine the effect of PAK Teachers' Professional Competence on the Learning Interest of Class IX Students of SMP Negeri 2 Nainggolan for the 2023/2024 Academic Year. The method used is quantitative with descriptive statistics with a population of all grade IX students of SMP Negeri 2 Nainggolan for the 2023/2024 Academic Year totaling 65 people and set the sample to be total so that it is a population study. Data was collected with a positive closed questionnaire of 40 items. The results of the data analysis show that there is an influence of PAK Teacher Professional Competence on the Learning Interest of Class IX Students of SMP Negeri 2 Nainggolan for the 2023/2024 Academic Year: 1) Test the analysis requirements: a) test the relationship between variable X and variable Y obtained the value rxy = 0.776 > rtabel(=0.05; IK=95%; n = 65) = 0.244 thus it is known that there is a positive relationship between variable X and variable Y. 2) Influence test: a) Regression equation test, obtained regression equation Ŷ = 18.917 + 0.738X. b) Regression coefficient of determination test (r2) = 60.2%. 3) Test the hypothesis using the r test obtained by calculating > rtable, which is 0.776 > 0.244. Thus, the hypothesis put forward in this study can be accepted, namely that there is an influence of PAK Teacher Professional Competence on the Learning Interest of Class IX Students of SMP Negeri 2 Nainggolan for the 2023/2024 Academic Year. The implication of the research results is that if to increase students' interest in learning, PAK teachers must improve their professionalism.